IDENTIFIKASI IKAN KERAPU Di PERAIRAN PANTAI BARAT SULAWESI SELATAN SEBAGAI ACUAN PEMILIHAN SPESIES POTENSIAL UNTUK BUDIDAYA PERIKANAN PANTAIIDENTIFICATION OF GROUPERS AT WEST COASTAL WATERS OF SOUTH SULAWESI AS REFERENC - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
This experiment was conducted to identify potensial grouper species for coastal aquaculture and high price at global markets. Fish samples of 30 individuals were collected every month during 7 months at landing places (LP) and markets at Barru, and Takkalasi (Barru Regency), Pangkajene (Pangkep Regency), and Parepare (Parepare Municipality). Fish samples were collected and placed in ice box than were identified and measured total length (TL) and body weight (BW). The results that consisted of 25 species belonged to 6 genera i. e. Aethaloperca, Anyperodon, Cephalopholis, Epinephelus, Plectropomus, and Variola. The biggest size was greasy grouper, E. tauvina (TI 66.0 cm